PENGARUH PELAYANAN PERPUSTAKAAN TERHADAP KEPUASAN SISWA DI SMPN 13 MAKASSAR - amalia, Andi; Mappincara, Andi; Basri, Syamsurijal (UNM (Universitas Negeri Makasar), 2023)
The aims of this study are to find out the description of library services at SMPN 13 Makassar, to find out the description of student satisfaction with library services at SMPN 13 Makassar, to find out that there is an influence between library services on student satisfaction in library services at SMPN 13 Makassar. The approach of this research is a quantitative approach with a total sample of 100 class IX students using accidental random sampling technique. The instrument used was a questionnaire with student respondents. Instrument development through the validity of instumen experts by way of instrument trials.. Analysis using inferential analysis. The results showed thaat the description of library services tends to be in the high category, the description of student satisfaction tends to be in the high category, there is a significant influence between library services on student satisfaction at SMPN 13 Makassar.